1997
DOI: 10.1128/jvi.71.1.800-806.1997
|View full text |Cite
|
Sign up to set email alerts
|

Infection of primary cultures of human neural cells by human coronaviruses 229E and OC43

Abstract: We evaluated the ability of human coronaviruses to infect primary cultures of human neural cells. Double immunofluorescence with antibodies to virus and cell markers showed infection of fetal astrocytes and of adult microglia and astrocytes by strain OC43. RNA amplification revealed infection of fetal astrocytes, adult microglia, and a mixed culture of adult oligodendrocytes and astrocytes by strain 229E. Infectious virus was released only from fetal astrocytes, with higher titers for OC43. Human coronaviruses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
0
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 25 publications
5
82
0
2
Order By: Relevance
“…Up until now, no clear specific association has ever been made with any known human neuropathology. However, even though the mechanism by which they reach the human CNS is still to be decrypted, at least three of the six coronaviruses that infect humans were shown to be neuroinvasive and neurotropic in humans: HCoV-229E and HCoV-OC43 (Arbour et al, 1999a(Arbour et al, , 1999b(Arbour et al, , 2000Bonavia et al, 1997), as well as SARS-CoV (Gu et al, 2005;Xu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Up until now, no clear specific association has ever been made with any known human neuropathology. However, even though the mechanism by which they reach the human CNS is still to be decrypted, at least three of the six coronaviruses that infect humans were shown to be neuroinvasive and neurotropic in humans: HCoV-229E and HCoV-OC43 (Arbour et al, 1999a(Arbour et al, , 1999b(Arbour et al, , 2000Bonavia et al, 1997), as well as SARS-CoV (Gu et al, 2005;Xu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These ubiquitous but not well studied viruses have been associated with 30% of common colds in humans (Myint, 1995). Experimentally, both the 229E and OC43 prototype strains can infect human astrocytes and microglia in primary cultures (Bonavia et al, 1997) and their RNA was detected in a significant proportion of human autopsy brain samples Arbour and Talbot, unpublished results), which is consistent with their neurotropic potential. In clinical studies, various reports have associated human coronaviruses with nosocomial respiratory infections in premature newborns, as diagnosed by indirect immunofluorescence (Sizun et al, 1995), and enterocolitis in neonates with evidence of human coronaviruses shown by electron microscopy (Chany et al, 1982).…”
Section: Introductionmentioning
confidence: 61%
“…The technique we used would be more appropriate for treating a large number of human samples containing few cells. We have already reported the use of the RT-PCR technique with clinical samples Bonavia et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, human coronaviruses (HCoV) and virus-specific antibodies have been detected respectively in the brain and cerebrospinal fluids of MS patients (Burks et al, 1980;Murray et al, 1992;Stewart et al, 1992;Arbour et al, 2000;Salmi et al, 1982). Furthermore, acute infection of human microglia and astrocytes in primary cultures (Bonavia et al, 1997) and persistent infection of CNS cell lines (Arbour et al, 1999a,b) both demonstrate the neurotropism of human coronavirus.…”
Section: Introductionmentioning
confidence: 99%